A study of successive over-relaxation method parallelisation over modern HPC languages. (1st January 2014) - Mittal, Sparsh
Successive over-relaxation (SOR) is a computationally intensive, yet extremely important iterative solver for solving linear systems. Due to recent trends of exponential growth in the amount of data generated and increasing problem sizes, serial platforms have proved to be insufficient in providing the required computational power. In this paper, we present parallel implementations of red-black SOR method using three modern programming languages namely Chapel, D and Go. We employ SOR method for solving 2D steady-state heat conduction problem. We discuss the optimisations incorporated and the features of these languages which are crucial for improving the program performance. Experiments have been performed using two, four, and eight threads and performance results are compared with those obtained using serial execution. The analysis of results provides important insights into the working of SOR method.